Higher Mobility and Carrier Lifetimes in Solution‐Processable Small‐Molecule Ternary Solar Cells with 11% Efficiency. Issue 7 (20th December 2018) - Liang, Ru‐Ze; Zhang, Yiming; Savikhin, Victoria; Babics, Maxime; Kan, Zhipeng; Wohlfahrt, Markus; Wehbe, Nimer; Liu, Shengjian; Duan, Tainan; Toney, Michael F.; Laquai, Frédéric; Beaujuge, Pierre M.
Abstract: Solution‐processed small molecule (SM) solar cells have the prospect to outperform their polymer‐fullerene counterparts. Considering that both SM donors/acceptors absorb in visible spectral range, higher expected photocurrents should in principle translate into higher power conversion efficiencies (PCEs). However, limited bulk‐heterojunction (BHJ) charge carrier mobility (<10 ‐4 cm 2 V ‐1 s ‐1 ) and carrier lifetimes (<1 µs) often impose active layer thickness constraints on BHJ devices (≈100 nm), limiting external quantum efficiencies (EQEs) and photocurrent, and making large‐scale processing techniques particularly challenging. In this report, it is shown that ternary BHJs composed of the SM donor DR3TBDTT (DR3), the SM acceptor ICC6 and the fullerene acceptor PC71 BM can be used to achieve SM‐based ternary BHJ solar cells with active layer thicknesses >200 nm and PCEs nearing 11%. The examinations show that these remarkable figures are the result of i) significantly improved electron mobility (8.2 × 10 ‐4 cm 2 V ‐1 s ‐1 ), ii) longer carrier lifetimes (2.4 µs), and iii) reduced geminate recombination within BHJ active layers to which PC71 BM has been added as ternary component. Optically thick (up to ≈500 nm) devices are shown to maintain PCEs >8%, and optimized DR3:ICC6:PC71 BM solar cells demonstrate long‐term shelf stability (dark) for >1000 h, in 55% humidity air environment. Abstract : Small‐molecule‐based ternary BHJ solar cells with the SM donor DR3, the SM acceptor ICC6, and the fullerene PC71 BM yield high power conversion efficiencies nearing 11% for active layer thicknesses >200 nm. With low geminate and nongeminate recombination, long carrier lifetimes, and high/balanced carrier mobilities, the ternary system maintains PCEs >8% over a wide range of active layer thicknesses within 200–500 nm.